أثر ضغوط العمل على أخلاقيات المهنة - آسية, خميس; شيماء, حميدي; مروة, طرية (جامعة الوادي - University of Eloued, 2023)
"هدفت هذه الدراسة إلى التعرف على أثر ضغوط العمل على أخلاقيات المهنة والالتزام بهذه الأخيرة لدى عمال مؤسسة سوناطراك ( محطتي الضخ رقم 01 ورقم 02 )- بجامعة ولاية المغير، ولتحقيق أهداف الدراسة تم اختيار عينة من هذه المؤسسة الاقتصادية. وقد تم توزيع 100 استبيان، حيث تم تحليل البيانات الواردة في الاستبيانات عن طريق استخدام برنامج الحزمة الإحصائية للعلوم الاجتماعية (SPSS) والمتوسطات الحسابية، الانحرافات المعيارية، تحليل الانحدار البسيط والمتعدد، وخلصت الدراسة إلى العديد من النتائج أهمها : يوجد أثر سلبي لأبعاد ضغوط العمل على أخلاقيات المهنة في مؤسسة سوناطراك ( محطتي الضخ رقم 01 ورقم 02 ) بجامعة ولاية المغير، مستوى ضغوط العمل ودرجة الالتزام بأخلاقيات المهنة مرتفع في المؤسسة.كما أنه لا توجد فروق ذات دلالة إحصائية في تصور عمال المؤسسة حول أخلاقيات المهنة تُعزى إلى المتغيرات الشخصية. " "This study aimed to identify the impact of work pressures on professional ethics and commitment to the latter among the workers of the Sonatrach Corporation (pumping stations No 01 and No 02) at Djamaa , and to achieve the objectives of the study, a sample of this economic institution was chosen. 100 questionnaires were distributd, where the data contained in the questionnaires were analyzed by using the Statistical Package for Social Sciences (SPSS) program, arithmetic averages, standard deviations, and simple and multiple regression analysis, and the study concluded with many results,the most important of which are : There is a negative effect of the dimensions of work pressures on professional ethics in the Sonatrach institution (pumping stations No 01 and No 02) a Djamaa at Al-Mogheir, the level of work pressure and the degree of commitment to professional ethics are high in the institution.There are no statistically significant differences in the perception of enterprise workers about professional ethics, due to personal variables."
Keywords: ضغوط العمل، أخلاقيات المهنة، مؤسسة سوناطراك.; Keywords :work pressures, professional ethics,Sonatrach Corporation.